NEERKURI BY SAGE THERAIYAR - A REVIEW ON SIDDHA WAY OF URINE EXAMINATION IN THE LIGHT OF CONTEMPORARY CLINICAL METHODS (International Journal of Ayurveda and Pharma Research, 2016)
The Siddha system is said to have emerged in antiquity, from the highly evolved consciousness of the Siddhars. The clarified intellect and heightened intuition of Sage Theraiyar, resulting from Yogic powers, enabled to expound to the world the signs of a disease in the Urine of a person in his treatise â€œTheraiyar Neerkuri Vaithyamâ€ a book that details urine examination findings for diagnostic and prognostic purposes. The present paper deals with scientific validation of Neerkuri (urine examination), an important diagnostic tool in Siddha system of medicine. The methodology of diagnosis in Siddha system is based on eight fold examination of pulse, tactile perception, tongue, color and complexion, speech, eyes, stools and urine. Of all these parameters, Urine examination has gained paramount importance next to pulse examination. This paper parallels analyses the signs of urine examination between a few quotes from Sage Theraiyar text and modern text. This is an attempt to understand the Siddha system of diagnosing pathological conditions which are a non-invasive, highly cost effective procedure which can be used for both diagnostic and prognostic purposes.